2021
DOI: 10.1021/acs.jpclett.1c00559
|View full text |Cite
|
Sign up to set email alerts
|

Surface Ligand Engineering for a Lead-Free Cs3Cu2Br5 Microcrystal-Based Humidity Sensor with a Giant Response

Abstract: Halide perovskites are potential humidity-detection materials due to their sensitivity to water, but the instability of traditional lead-based halide perovskites and the toxicity of Pb hinder further application in humidity sensing. Here, lead-free Cs 3 Cu 2 Br 5 perovskite microcrystals passivated by surface ligands (OLA and OAm) are used to prepare an environmentally friendly humidity sensor. The humidity sensing performance of the prepared sensors was tested, and the effect of surface ligands of perovskites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…This is due to the water molecules adsorbed on the surface of sensitive materials promoting the polarization effect and increasing the dielectric constant, resulting in a decrease in sensor impedance with increasing RH. 40 In contrast to this, when the working frequency is above 10 kHz, the impedance curves become flat, which indicates that the sensor almost cannot be influenced by the change in RH. This phenomenon can be interpreted as the water molecules adsorbed on the surface of sensitive materials cannot be polarized due to the fast change in the direction of the electrical field.…”
Section: Characterization Of the Materialsmentioning
confidence: 90%
See 1 more Smart Citation
“…This is due to the water molecules adsorbed on the surface of sensitive materials promoting the polarization effect and increasing the dielectric constant, resulting in a decrease in sensor impedance with increasing RH. 40 In contrast to this, when the working frequency is above 10 kHz, the impedance curves become flat, which indicates that the sensor almost cannot be influenced by the change in RH. This phenomenon can be interpreted as the water molecules adsorbed on the surface of sensitive materials cannot be polarized due to the fast change in the direction of the electrical field.…”
Section: Characterization Of the Materialsmentioning
confidence: 90%
“…The fabricated sensor showed a humidity response of 196 from 40 to 90% RH levels. 15 Farzaneh et al fabricated a Cu-doped TiO 2 film sensor that exhibited an enhanced response (80) compared with that of the pristine TiO 2 (40) sensor between 30 and 70% RH levels. 16 Mallick et al prepared a humidity sensor by spinning polylactic acid−titanium dioxide (PLA− TiO 2 ) onto interdigitated ITO/glass substrates.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] Huang et al obtained a lead‐free Cs 3 Cu 2 Br 5 ‐based humidity sensor with a giant response through surface ligand engineering, and its response/recovery time was 22/10 s, respectively. [ 29 ] Pi et al used lead‐free double‐perovskite material Cs 2 TeCl 6 as the reversible and fast‐responsive humidity sensor, which had a response/recovery time of 13.8/1.39 s, and it was used for monitoring human respiration. [ 27 ] As we know, the performance of humidity sensors has a great correlation with material size, and the smaller the size of the material, the larger the surface‐to‐volume ratio, leading to the more water molecules being contacted and the better sensor performance.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] Therefore, the lead-free perovskite has entered the vision of researchers due to its environmental friendliness. Meanwhile, a few kinds of the lead-free perovskite, such as Cs 2 BiAgBr 6 , Cs 2 TeCl 6 , Cs 2 PdBr 6 , and Cs 3 Cu 2 Br 5, [15,[24][25][26][27][28][29][30] have good water and oxygen stability; thus, they can work stably in the environment for a long time and have been used to prepare humidity sensors. Humidity sensors with high sensitivity and fast response play an important role in environmental, industrial, and agricultural fields for monitoring moisture content.…”
mentioning
confidence: 99%
“…Shaukat et al 17 have demonstrated a highly sensitive TiSi 2 based humidity sensor with all range linear humidity sensing performance. Yanyi Huang et al 18 have used halide perovskites as potential humidity-detection materials due to their sensitivity to water. Here lead-free Cs 3 Cu 2 Br 5 perovskite microcrystals are used to prepare an environmentally friendly humidity sensor.…”
Section: Introductionmentioning
confidence: 99%